Dynamic response and failure mechanism of Ti-6AL-4V hi-lock bolts under combined tensile-shear loading. (September 2019) - Liu, Xiaochuan; Xi, Xulong; Bai, Chunyu; Yang, Jialing; Yang, Xianfeng
Highlights: The dynamic mechanical behavior and failure characteristics of the Ti-6AL-4V hi-lock bolts were investigated under different loading conditions. The dynamic mechanical properties of the Ti-6AL-4V alloy material were studied at different strain rates. A novel experimental fixture and a new collision-type loading method are proposed. Three different failure modes were observed: fastener collar/bush pull-out failure mode, fastener shank shear failure mode and the mixed tensile-shear failure mode. A failure constitutive model was established to predict the failure behavior of HLB. Abstract: This paper is focused on the dynamic mechanical behavior and failure characteristics of Ti-6AL-4V hi-lock bolt (HLB) under combined tensile-shear loading. Firstly, the dynamic mechanical properties of Ti-6AL-4V alloy under the quasi-static, intermediate strain rate and high strain rate are investigated by using an electronic universal testing machine, a high velocity hydraulic servo-testing machine and Split Hopkinson Pressure Bar (SHPB). A Johnson-Cook model is established to describe the dynamic constitutive relationship of Ti-6AL-4V alloy on the basis of the experimental results. A novel experimental fixture and a new collision-type loading method are proposed to investigate the dynamic failure characteristics of HLB. The dynamic pure tensile, 30° tensile-shear coupling, 45° tensile-shear coupling, 60° tensile-shear coupling, pure shear experiments of HLB are conducted at the velocities of 0.01 m/s, 0.1 m/s and 1 m/s, respectively. Furthermore, a finite element model is established to validate the experimental results, and good agreement is obtained between the experimental and the simulation results. The experimental results show that the failure mode and the failure load of the HLB are greatly affected by the loading condition but less by the loading speed.